2008
DOI: 10.1007/s10038-007-0243-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of the serotonin transporter gene, neuroticism and smoking behaviours

Abstract: Cigarette consumption and smoking cessation are influenced in part by genes. Personality traits have also been implicated in the aetiology of smoking. Neuroticism, a personality trait with a heritable component, correlates well with anxiety and depression, increasing the risk of being a smoker and decreasing the chance of smoking cessation. Several prior studies in non-British populations have given conflicting results as to whether some genetic polymorphisms affect the relationship between smoking and neuroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Serotonin receptor signaling was enriched in the genes associated with SI/P and ND, but not SC, in our analysis. In several recent studies designed to investigate the association between genes from the serotonin receptor signaling pathway and SC, no positive result was obtained (Brody et al , 2005; David et al , 2008a; David et al , 2007b; Munafo et al , 2006; O'Gara et al , 2008). Similar to the serotonin receptor signaling pathway, tryptophan metabolism, the pathway involved in the biological synthesis of serotonin, is enriched in the genes associated with SI/P, but not in SC.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin receptor signaling was enriched in the genes associated with SI/P and ND, but not SC, in our analysis. In several recent studies designed to investigate the association between genes from the serotonin receptor signaling pathway and SC, no positive result was obtained (Brody et al , 2005; David et al , 2008a; David et al , 2007b; Munafo et al , 2006; O'Gara et al , 2008). Similar to the serotonin receptor signaling pathway, tryptophan metabolism, the pathway involved in the biological synthesis of serotonin, is enriched in the genes associated with SI/P, but not in SC.…”
Section: Discussionmentioning
confidence: 99%
“…Data suggested also that smoking behavior is influenced by an interaction between neuroticism and 5-HTTLPR genotype [ 32 ]. More recently, however, a number of studies demonstrated that although neuroticism and depression vulnerability were associated with smoking behavior, genotype did not affect this relationship [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A ‘reward deficiency syndrome’ has been postulated as one unifying theme to account for the role of diverse neurotransmitters in nicotine dependency [25], [26], [27], and consequently many studies have evaluated genes in opioid [28], [29], serotinergic [30], [31], [32], dopaminergic [26], [33], [34], [35], drug metabolizing enzyme [36], [37], [38], [39], [40], [41] and nicotinic and muscarinic cholinergic receptor pathways[42], [43]. Results from these studies have been largely equivocal, due to small sample sizes in individual studies, incomplete and non-overlapping genetic coverage, differences in measures of smoking behavior, or differences in genetic and environmental backgrounds.…”
Section: Introductionmentioning
confidence: 99%